2017
DOI: 10.1007/s00330-017-4926-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between MRI with MR cholangiopancreatography and endoscopic ultrasonography for differentiating malignant from benign mucinous neoplasms of the pancreas

Abstract: • The A values of MRI were higher than those of EUS. • The diagnostic accuracies of MRI were higher than those of EUS. • The specificities of MRI were higher than those of EUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…We have directly characterized human pancreatic tissue in a manner that can also be applied to engineered scaffolds for translational applications. Our characterization method has enabled us to confirm qualitative and quantitative findings that pancreatic tumors are stiffer than normal pancreas [3,52,53], but importantly, our system enables direct comparison to in vitro constructs that previous methods did not. Our values for elastic modulus of patient tissue were similar to direct mechanical characterization by mesoscale indentation (normal = 0.787 – 1.452 kPa and tumor = 1.885 – 13.70 kPa), and relative values for elastography showed similar trends.…”
Section: Discussionmentioning
confidence: 85%
“…We have directly characterized human pancreatic tissue in a manner that can also be applied to engineered scaffolds for translational applications. Our characterization method has enabled us to confirm qualitative and quantitative findings that pancreatic tumors are stiffer than normal pancreas [3,52,53], but importantly, our system enables direct comparison to in vitro constructs that previous methods did not. Our values for elastic modulus of patient tissue were similar to direct mechanical characterization by mesoscale indentation (normal = 0.787 – 1.452 kPa and tumor = 1.885 – 13.70 kPa), and relative values for elastography showed similar trends.…”
Section: Discussionmentioning
confidence: 85%
“…A combination of T2-HASTE and DWI has been shown to have similar accuracy to a comprehensive contrast-enhanced MRI protocol for the detection of pancreatic cancer. 43 A recent study suggested that MRI with MRCP has a better diagnostic performance than endoscopic ultrasound (EUS) for differentiating malignant from benign pancreatic IPMN and MCN, 44 but conclusive evidence is lacking.…”
Section: Recommendationsmentioning
confidence: 99%
“…Two recent studies have showed different results comparing both techniques. In one of them, MRI-MRCP was considered more sensitive for differentiating malignant from benign IPMN and mucinous cystic neoplasms (MCN) [12]. In the other study was also included contrast-enhanced CT, but significant difference was not observed [13] Larger series that compare EUS and MRI-MRCP in the surveillance population are therefore required.…”
Section: Introductionmentioning
confidence: 99%